MODEL OF HEALTH OF CREATIVE EDUCATIONAL SPACE OF PRESCHOOL INSTITUTION AS ENVIRONMENT OF DEVELOPMENT OF BASICS OF PHYSICAL CULTURE OF PRESCHOOL CHILDREN - Abdulmanova, L.V. (Pedagogy of Higher and Secondary Education, 2022)
No abstract.